Tommy John Surgery, Sports Medicine, and Baseball’s Rhetorics of Fair Play - John W. Jordan (Communication & Sport, 2026)
Tommy John Surgery (TJS) revolutionized baseball by repairing a previously career-ending injury. Its invention necessarily altered traditional narratives about athletic performance and decline, but John’s subsequently improved pitching gave rise to suspicions that TJS was an unnatural performance enhancement. John’s counterargument successfully enabled TJS to be approved by baseball, but undermined the seriousness of the surgery and the cause behind the injury. Doctors and former players are now calling for a change to the public discussion of TJS in an effort to prevent a possible “epidemic” of youth pitchers requiring the procedure. This call is hampered by the sterling reputation TJS enjoys, which is due largely to how John and Major League Baseball redrew the line between a medical “fix” and an unnatural “enhancement.”